The Functional Movement Screen and modified Star Excursion Balance Test as predictors of T-test agility performance in university rugby union and netball players. (May 2018) - Armstrong, Ross; Greig, Matt
Abstract: Objectives: Agility is a functional requirement of many sports, challenging stability, and commonly cited as a mechanism of injury. The Functional Movement Screen (FMS) and modified Star Excursion Balance Test (mSEBT) have equivocally been associated with agility performance. The aim of the current study was to establish a hierarchical ordering of FMS and mSEBT elements in predicting T-test agility performance. Design: Cross-sectional study design. Setting: University. Participants: Thirty-two female rugby players, 31 male rugby players and 39 female netballers Main Outcome Measures: FMS, mSEBT, T-test performance. Results: The predictive potential of composite FMS and mSEBT scores were weaker than when discrete elements were considered. FMS elements were better predictors of T-test performance in rugby players, whilst mSEBT elements better predicted performance in netballers. Hierarchical modelling highlighted the in-line lunge (ILL) as the primary FMS predictor, whereas mSEBT ordering was limb and sport dependent. Conclusions: The relationship between musculoskeletal screening tools and agility performance was sport-specific. Discrete element scores are advocated over composite scores, and hierarchical ordering of tests might highlight redundancy in screening. The prominence of the ILL in hierarchical modelling might reflect the functional demands of the T-test. Sport-specificity and limb dominance influence hierarchical ordering of musculoskeletal screens. Highlights: The in-line lunge was the primary predictor of T-test performance. FMS elements were a better predictor of T-test performance in rugby than netball. mSEBT elements were a better predictor of T-test performance in netball than rugby. Composite mSEBT score revealed stronger correlations in the netball than rugby. Discrete element scores are advocated over composite scores for the FMS and mSEBT.